Early and mature biofilm on four different dental implant materials: An in vivo human study. Issue 11 (29th September 2020) - Herrmann, Henrike; Kern, Jaana‐Sophia; Kern, Thomas; Lautensack, Julia; Conrads, Georg; Wolfart, Stefan
Abstract: Objectives: The aim of this study was to examine the microbial composition of early (after 3 days, D3 ) and mature biofilms (after 31 days, D31 ) on materials typically used in implant/abutment buildups. Implant/abutment materials with different surface roughness values (Ra ) were compared to detect differences in the quantity and quality of bacterial composition. Material and Methods: Four different materials were investigated: rough implant surface (sand‐blasted acid‐etched titanium, Ti‐p ), implant collar (machined titanium, Ti‐m ), titanium abutment ( Ti6Al4V ), and zirconium dioxide abutment ( ZrO2 ). Fourteen periodontally healthy subjects received mandibular acrylic devices with four disks (one for each material) facing the anterior lingual area. The total bacterial count was analyzed using RT‐qPCR. Both presence and proliferation of 20 selected bacterial species were assessed with microarrays. Results: The highest mean total cell counts (x10 8  ± standard deviation) were detected at D3 on ZrO2 (5.63 ± 4.83; Ra  = 0.74 µm), followed by Ti‐p (4.53 ± 5.00; Ra  = 1.87), Ti–m (4.43 ± 9.38; Ra  = 0.18 µm), and Ti6Al4V (3.83 ± 3.13; Ra  = 0.16 µm). ZrO2 showed significantly higher total bacterial cell counts than Ti‐p and Ti‐m ( p  < .05) for both time intervals. The microarrays detected 16 (D3) and 17 (D31) bacterial species; those associated with healthy oral microbiotas, but also bacteria of the red complex ( Tannerella forsythia, Treponema denticola ), were found on all materials. Conclusions: Biofilms on ZrO2 harbored a higher total number of bacterial cells compared with those formed on titanium surfaces with much lower roughness values. Putative periodontopathogens were detected on all materials after both time intervals. Implant/abutment materials with a low surface roughness showed less biofilm accumulation.